Neuroinflammation induced by amyloid beta 1‐42 oligomers contributes to neuronal loss in an in vitro model of Alzheimer's disease. (1st February 2022) - Henriques, Alexandre; Rouvière, Laura; Griesbeck, Anne; Schmidt, Ronny; Schroeder, Christoph; Farrugia, Clémence; Poindron, Philippe; Callizot, Noelle
Abstract: Background: Alzheimer's disease is characterized by the extracellular accumulation of senile plaques composed of amyloid beta and the intracellular deposition of neurofibrillary tangles composed of hyperphosphorylated tau. Soluble oligomers of Aβ 1‐42 peptide (AβO) are neurotoxic and participate directly in the pathophysiology of Alzheimer's disease. Here, we studied the contribution of microglial activation in the human 1‐42 AβO‐induced neurotoxicity, in an in vitro model of Alzheimer's disease. Method: Using primary mixed cultures of rat embryonic cortical neurons and microglial cells, AβO toxicity was investigated in presence or absence of TLR4 antagonist (TAK‐242). Survival of cortical neurons, integrity of their neurite network and activation of microglial cells were studied by immunostaining. In addition, proteomic changes were investigated using an immuno‐based protein assay covering 1300 proteins including inflammatory related proteins, immune cell marker, checkpoint molecules as well as mediators and signaling molecules related to apoptosis and necroptosis among many others. Result: We showed that AβO application led to an activation of microglial cells, a release of pro‐inflammatory cytokines and a chronic neurotoxicity. Neuronal loss was significantly reduced but not abolished in presence of an inhibitor of TLR4. In addition, protein expression analysis revealed major enrichments in protein pathways related to cytokine signaling. Conclusion: Altogether, these findings showed that the toxicity of AβO is partially due to the activation of microglial cells and the release of pro‐inflammatory cytokines. It highlights the close pathological connection between AβO microglial cells, neuroinflammation and neuronal death in Alzheimer's disease.